Upaya Indonesia Menjaga Keamanan Pangan (Food Security) melalui Paris Agreement of Climate Change - Kinanti, Alyandani Ayu; Yulianti, Dina (Universitas Diponegoro, 2023)
Indonesia, having affected by the climate change, has a national interest to sign the Paris Agreement of Climate Change. The disruption of food security as a consequence from climate change raises Indonesia's interest on participating in the Paris Agreement. Indonesia's Nationally Determined Contributions report, which was last compiled in 2021, shows its contribution as a Party by committing to carry out mitigation and adaptation actions related to food security as a result of climate change. Analyzed through the four dimensions of food security according to the Food and Agriculture Organization (FAO), Indonesia's mitigation and adaptation action programs in the 2021's NDCs are considered to fulfill these four dimensions and will gradually maintain food security if implemented in a sustainable manner. It can be concluded that Indonesia has shown its commitment and contribution in maintaining food security as a member of the Paris Agreement.